The influence of research and publications on conventional wisdom and policies affecting forests - Spilsbury, M.J.; Kaimowitz, D. (2000)
Funding agencies expect policy researchers to show that their efforts have a measurable impact. This poses a considerable challenge. It was traditionally thought that research influences policy directly and that specific policies can be traced back to particular research findings. However, many analysts have now come to regard the link between research and policy as more diffuse: research induces changes in "conventional wisdom" (the set of dominant paradigms at a given moment regarding the desired ends of policy and the means of achieving them) and "policy narratives" (simplifying assumptions about the problem to be addressed and the approach to be taken), which in turn influence policy outcomes. Given the bewildering array of factors that influence policy-makers' decisions, it would be naïve to overestimate the role of knowledge acquisition in that process. A role exists nonetheless. This article combines a theoretical discussion of how policy-makers utilize research with a pragmatic attempt to find out what research has been influential. Between December 1997 and March 1998, the authors asked forest policy experts by e-mail which publications influenced international and national debates on policies that affect forests. The survey elicited 162 replies. The article analyses those responses in the context of the broader debate on the link between research and policy.